KENYAMANAN TERMAL RUANG LUAR DI KORIDOR JALAN TUGU-KRATON KOTA YOGYAKARTA - , ARDINA PUTRI RAHTAMA; , M. Sani Roychansyah, ST., M.Eng., D.Eng. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The research of outdoor thermal comfort in Tugu-Kraton Street Corridor Yogyakarta City is important to do. Urban heat island makes thermal comfort declined. Outdoor is a place often used carrying out social interaction. Outdoor thermal comfort is depended on its enclosure. Study has objectives to measure thermal comfort degree and identify its factors. In addition, study also identifies enclosureâs influence towards outdoor thermal comfort. Study uses a mixed deductive method. Quantitative analysis is used to measure thermal comfort. Qualitative analysis is used to relate enclosureâs influence to microclimate condition of the corridor. Study got 256 respondents who have been doing activity in Tugu-Kraton Street Corridor. Interpretation of microclimate data and respondentâs characteristic was done in the same time. The result of study indicates that Tugu-Kraton Street Corridor isnât comfortable. It is indicated by PET value 37,96Â°C. PET value shows outdoor thermal comfort standard in Tugu-Kraton Street Corridor at person in the age of 35 years old, 57 kg in weight, and 170 cm in height when he/she is doing activity as big as 1,1 met with clothes 0,52 clo, air temperature 31Â°C, mean radiant temperature 39Â°C, solar radiation 51,11 W/m2, air humidity 57,47%RH and wind velocity 0,11 m/s. Youngster prefer colder microclimate than children and old people do. Thermal comfort in Tugu-Kraton Street Corridor is mostly influenced by air temperature, air humidity, and wind velocity. Comfortable outdoor tends to have bright colored buildings, wide setback, a lot of wide crown trees, paved floor, a lot of street furniture, and closed sky view factor.